Дискурсивное изучение особенностей языка религии - Abubakirova, A.; Dilbarkhanova, D. (Eurasian Journal of Religious Studies, 2021)
At present, religion is integrated into almost all spheres of human life, has experienced a period of revival, and is developing in a new direction. Therefore, the discursive study of religious issues, that is, the analysis of issues related to religion in the context of modern discourse, is an important and relevant area of research. Considering that the purpose of this study is to identify and describe the features of the concept of language according to its nature and use in a religious context, which is closely related to the concept of religion, the main areas of research include religious studies and linguistic views, and it is aimed at demonstrating that the differences between the language of religion and language of everyday use directly contribute to its ability to influence the consciousness of believers, fully conveying religious statements. Research results are important because they show the characteristics and ways of conducting discourse analysis and can help in applying these results. The study used a variety of general and individual scientific methods. The features of the language of religion are revealed, conclusions about their meaning and use are analyzed, a general and complete picture of the language of religion is formed. Knowledge of the general characteristics and capabilities of the language of religion helps to find solutions to many religious problems and prevent them. Key words: language, language of religion, sign, symbol, linguistics, religious philosophy.